Decorative interiors between craft and digital design (CNC) in interior spaces - Mozan, Basim Mahdi; Abdul Razzaq, Harith Asaad (Al-Adab Journal, 2021)
In order to reach the basic building blocks of the research topic tagged "Decorative Decors between Crafts and Digital Design (CNC) in Interior Spaces", the research problem identified the lack of a complete vision among designers in employing digital technologies in harmony with the art of traditional handcraft in manufacturing decorative decors in interior space , And the research goal was to discover the differences between the features of handicraft and the advantages of digital manufacturing and ways of combining traditional techniques among handcraft craftsmen with the innovative digital techniques (CNC) in the interiors executed in the interior spaces. As well as defining the research boundaries, which were represented by the subject matter ranges according to the field of interior design within the buildings of the presidents of Iraqi universities in Baghdad, which were redesigned within the period (2014-2018). As for the theoretical framework, it included a study: Introduction to decorative and decorative designs between craft and digital design (CNC) in interior design. The research also included research procedures from adopting the descriptive approach and choosing the community consisting of public universities in the city of Baghdad, and how to elect the sample from it, as well as building the research tool and showing its validity and testing its stability by researchers and external analysts. After applying the tool to the selected models for the purpose of analysis, we have a set of results, the most important of which are: -The decorative decorations implemented literally showed a human relationship through the craftsman's handling of the raw material and the resulting errors in implementation, whether intended or unintended, and the loss of this relationship in the digitally executed decorations where possible production.The decorations executed were literally characterized by being non-repeatable artistic pieces, and if they were repeated, they will not be in the same shape 100%, which characterizes the literal work (uniqueness), with the ability to produce very large quantities of the executed designs with digital technology and with a 100% match. After that, the research came out with several conclusions, and then a number of recommendations were put forward, as well as several research proposals complementing our current research as well as identifying the beneficiaries as fields of work that enable us to apply the applied outputs from our current research and thus, we have completed our current research and achieve the goal set for it.